Secondary students with special needs and social acceptability in regular classrooms - Sarao, Virzon L. (2008)
This qualitative study looked into the frequency of choosing students with special needs to participate in socialization/classroom activities, dimensions of social acceptance (as seatmate, team mate, companion, group mate, and workmate) the SSNs were chosen, and the reasons of regular students for SSNs acceptance or non-acceptance. The sociometric test, checklist of autism-spectrum-indicator encounter, and random interview were used to gather data. The findings of the study revealed that regular students accepted SSNs as seat mates and workmates but, they were rejected as team mates, companions and group mates. Social acceptance requires greater exposure and opportunities of regular students to interact with SSNs in activities, characterized by exchanges of benefits, prefers someone with shared similar personality and someone who can help or contribute ideas.